2022
DOI: 10.3390/cancers14153574
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Splenic Volume Outweighs Immuno-Modulated Size Changes with Regard to Survival Outcome in Patients with Hepatocellular Carcinoma under Immunotherapy

Abstract: Background: An association between immunotherapy and an increase in splenic volume (SV) has been described for various types of cancer. SV is also highly predictive of overall survival (OS) in patients with hepatocellular carcinoma (HCC). We evaluated SV and its changes with regard to their prognostic influence in patients with HCC undergoing immunotherapy. Methods: All patients with HCC who received immunotherapy in first or subsequent lines at our tertiary care center between 2016 and 2021 were screened for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Again, Lukas Müller at all [ 21 ]. found that a large proportion of hepatocellular carcinoma (HCC) patients who received immunotherapy treatment as first-line therapy had an increase in splenic volume after initiation of immunotherapy, but this was not associated with survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Again, Lukas Müller at all [ 21 ]. found that a large proportion of hepatocellular carcinoma (HCC) patients who received immunotherapy treatment as first-line therapy had an increase in splenic volume after initiation of immunotherapy, but this was not associated with survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022 Müller et al investigated for the first time the change in SV in a cohort of 55 patients with HCC receiving IO [ 17 ]. They demonstrated a significant correlation of high baseline splenic volume (SV) with impaired OS (4.0 months vs. 30.7 months, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…SV was assessed using an established tool for fully automated segmentation and volumetry of the spleen as described previously [ 16 ]. This algorithm employs the open-source MIScnn library, a convolutional neural network with a U-Net architecture, and has previously been trained for spleen segmentation in patients with HCC undergoing transarterial chemoembolization (TACE) [ 20 ] as well as patients with HCC under IO [ 17 ]. Further detailed information on the features of the network, the settings for training and validation, and the model’s performance can be found in the original publication [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Castagnoli et al 20 negated the predictive value of SV in treatment response among patients who underwent immunotherapy for non–small-cell lung cancer. Muller et al 21 noted that an increase in SV before and throughout immunotherapy served as a major predictive factor of poor overall survival (OS) in patients with advanced HCC. However, few studies have compared the role of SV changes in patients undergoing treatment with ICIs or sorafenib for advanced HCC.…”
Section: Introductionmentioning
confidence: 99%